2023
DOI: 10.1021/acs.langmuir.3c00879
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Immobilization of Multi-Enzymes for Enhanced Substrate Channeling of Enzyme Cascade Reactions: A Nanoarchitectonics Approach by Directed Metal–Organic Frameworks

Abstract: Rationally tailoring a controlled spatial organization of enzymes in a nanoarchitecture for multienzyme cascade reactions can enhance the catalytic efficiency via substrate channeling. However, attaining substrate channeling is a grand challenge, requiring sophisticated techniques. Herein, we report facile polymerdirected metal−organic framework (MOF)-based nanoarchitechtonics for realizing a desirable enzyme architecture with significantly enhanced substrate channeling. The new method involves the use of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In this study, they found that compared to subsequent immobilization, the one-step immobilization technique results in higher cascade enzymatic activity (Figure 7c). The utilization of PADD also increases the enzyme catalytic activity, 1.5 higher compared to the immobilized enzymes without PADD (Figure 7d) [84]. The covalent immobilization of enzymes on the surface of functionalized MOFs has also been described, in addition to immobilization through encapsulation or coprecipitation.…”
Section: One-step Co-immobilization Of Enzymes Using Mofmentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, they found that compared to subsequent immobilization, the one-step immobilization technique results in higher cascade enzymatic activity (Figure 7c). The utilization of PADD also increases the enzyme catalytic activity, 1.5 higher compared to the immobilized enzymes without PADD (Figure 7d) [84]. The covalent immobilization of enzymes on the surface of functionalized MOFs has also been described, in addition to immobilization through encapsulation or coprecipitation.…”
Section: One-step Co-immobilization Of Enzymes Using Mofmentioning
confidence: 81%
“…In this study, they found that compared to subsequent immobilization, the one-step immobilization technique results in higher cascade enzymatic activity (Figure 7c). The utilization of PADD also increases the enzyme catalytic activity, 1.5 higher compared to the immobilized enzymes without PADD (Figure 7d) [84].…”
Section: One-step Co-immobilization Of Enzymes Using Mofmentioning
confidence: 90%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was used to confirm the purification of PepD. The PepD concentration was determined by the Bradford method …”
Section: Methodsmentioning
confidence: 99%
“…8,9 While little is known about a given enzyme environment and its exact conformation during MOF formation, enzymatic tertiary structure, location, and orientation within the crystal are known to play key roles in the activity of the immobilized enzyme. 10–12…”
Section: Introductionmentioning
confidence: 99%